Assyria: the imperial mission - Liverani, Mario (Mesopotamian civilizations, 2017)
Imperialism : materiality and ideology -- God's will -- Communicating with God -- Holy war and just war -- Exploring and conquering -- The disposable periphery -- Collecting -- Public display -- Marking territory : the steles -- Celebrative inscriptions -- Royal titulature -- The justification of self-defense -- Battles and sieges -- Oaths and their transgression -- Punishment and forgiveness -- Destruction and reconstruction -- Exporting despotism -- Organizing the territory : (a) the city at the center of the world -- Organizing the territory : (b) provinces and governors -- Organizing the territory : (c) from tributaries to deportees -- Organizing the territory : (d) the communication network -- Becoming Assyrian -- Imperial prosperity -- Cultural unification : (a) technology -- Cultural unification : (b) religion -- Cultural unification : (c) language -- Conclusions : (a) the prototype empire -- Conclusions : (b) trajectories of imperialism -- Ancient and modern empires -- Conclusions : (c) celebration and reality -- The view of others